Membrane treatment of wastewater from oil and gas production: motivations and material innovation - Du, Xuewei, author; Tong, Tiezheng, advisor; Carlson, Kenneth, committee member; Sharvelle, Sybil, committee member; Kota, Arun Kumar, committee member (Colorado State University. Libraries, 2022)
The rise of shale oil and gas (O&G) via hydraulic fracturing (HF) has boosted energy production in the United States. Further, many of the U.S. shale plays coincide with water-scarce areas that suffer from prolonged drought periodically. The substantial volumes of water consumption and wastewater generation associated with O&G activities intensify local water stress and create a challenge of wastewater management, rendering treatment and reuse of O&G wastewater an essential strategy to improve water sustainability of O&G-producing regions. Herein, the main goal of this dissertation is to facilitate the reuse and treatment of O&G wastewater in order to promote water sustainability of O&G-producing regions. To achieve this goal, two sets of studies were performed, which pertain to (1) data analysis to investigate the water footprint of O&G production under hydrodynamic variation; and (2) developing novel membrane materials for more efficient O&G wastewater treatment. First, I investigated the relationship of hydroclimate variation with the activities and water footprint of O&G production in Colorado, one of the major O&G producing states in the U.S. I discovered that hydroclimate variation imposes a negligible impact on well number and water footprint of O&G production. However, the intensive water consumption by HF under arid conditions could escalate competition for water resources at the local scale. Further, I expanded the research scope to estimate the water consumption by HF activities under different hydroclimate conditions in eleven O&G-producing states in the central and western U.S. from 2011 to 2020. The results show that the water consumption under abnormally dry or drought climates accounted for 49.7% (475.3 billion gallons) of total water usage of HF, with 9% (86.1 billion gallons) of water usage occurred under extreme or exceptional drought conditions. The water usage of HF under arid conditions can translate to high densities of water footprint at the local scale, equivalent to more than 50% of the annual water usage by the irrigation and domestic sectors in 21-47 and 11-51 counties (depending on the specific year), respectively. Such water stress imposed by O&G production, however, could be effectively mitigated by the reuse of flowback and produced water. This renders wastewater reuse necessary to maintain water sustainability of O&G-producing regions in the context of both a rising O&G industry and a changing climate. Second, I focused on developing novel membrane materials for the treatment of O&G wastewater by membrane distillation (MD), which is an emerging technology showing promise for efficient desalination of high salinity industrial wastewater. I investigated the impacts of membrane surface wettability on the treatment of O&G wastewaters by MD. From this study, omniphobic membranes with high wetting resistance showed more robust performance, but they also required the use of toxic long-chain per- and polyfluoroalkyl substances (PFASs, ≥ 8 fluorinated carbons) during fabrication process and displayed lower water productivity compared to conventional hydrophobic membranes. Then, I developed highly wetting-resistant MD membranes while avoiding the use of long-chain PFASs, which is essential to improve the viability of MD for resilient and sustainable MD desalination. I demonstrated that long-chain PFASs are not required when designing membranes with high wetting resistance. Instead, the combination of hierarchical texture and (ultra)short-chain fluorocarbons are able to create MD membranes with exceptional wetting resistance. Finally, I also elucidated the fundamental relationship between membrane wetting resistance and water vapor permeability in the MD process, which needs to be taken into consideration when designing and selecting appropriate membranes for effective MD treatment of O&G wastewater. I identified that a trade-off exists between wetting resistance and water vapor permeability of MD membranes, and also unveiled the mechanism of such a trade-off by revealing the importance of water-air interfacial area in regulating water vapor transport through microporous membranes. I envision that the novel insights on omniphobic membrane fabrication and the wetting resistance-vapor permeability trade-off will pave the way for more rational design of MD membranes for sustainable O&G wastewater treatment applications.
Keywords: hydraulic fracturing; oil and gas wastewater; drought climates; omniphobic membrane; membrane distillation